Desenvolvimento de equipamento automatizado de baixo custo para quantificação de gás em tempo real - Souza, Rodrigo Santos (2022)
From the concept of what is waste, and the way in which society's consumerism increases its generation, and as such waste is usually disposed of irregularly, it is possible to structure the feasibility of installing means that can mitigate possible environmental impacts caused by the wrong disposal of this “garbage”. In parallel, there has been the development of several premises based on public policies (such as RenovaBio and PNRS) that over the last decade began to take effect, promoting and regulating practices that involve the correct disposal of waste, and the application of technologies for the development of sustainable practices. These practices, in addition to the correct disposal of waste, can also generate biofuels, such as biogas, which takes place in anaerobic reactors through the conversion of organic matter by microorganisms into gases such as methane and carbon dioxide. These gases, in turn, can be used to generate electricity, among other applications. In order to know the potential of biogas generation, tests, called BMP, are used. However, these laboratory tests usually do not have any automation, or have a high cost associated with data collection. Thus, the study is applied in order to develop a new system to quantify gas generation, in a fully automated and low-cost way. For this, microcontrollers and pressure sensors were used, which capture data every 4 seconds, and transfer them to Excel, where gas generation curves can be generated in anaerobic reactors in simulated situations, with the use of glucose and commercial yeast. The results found in the validation phase encourage the use of the system for gas quantification. Then, the prototype was submitted to the Central Composite Design, with adjustment to the Gompertz model, and through the ANOVA tool, it returned significant statistical values ​​for the measurement of the maximum gas generation rate (Rm), however, the values ​​found for the lag phase and for the final gas production, did not have statistical significance, for reasons unrelated to the prototype's ability to measure gas generation.